Mn-DOPPED ZnS QUANTUM DOTS AS SENSITIVE SENSOR FOR DETERMINATION OF CIPROFLOXACIN IN PHARMACEUTICAL AND BIOLOGICAL SAMPLES - Mian Muhammad; Behisht Ara; Faiz Ali; Izaz Ahmad; Hafeez Ullah (Journal of the Chilean Chemical Society, 2021)
A simple and fast spectrofluorimetric method for determination of ciprofloxacin based on its quenching effect on the fluorescence intensity of colloidal water soluble TGA caped, Mn doped ZnS quantum dots (QDs) has been described. The QDs having characteristic fluorescence spectra with maximum excitation at 315 nm followed by an emission peak at 632 nm were characterized using Energy Dispersive X-Ray and X-ray Diffraction techniques. The effect of various parameters such as concentration of QDs, time, pH, common excipients and metal ions on the quenching phenomenon was investigated. Fluorescence quenching was found to be maximum with 10 µg mL-1 of QDs at pH 8 and fluorescence intensity was observed to be constant upto 45 min. The Stern-Volmer calibration plot of F0/F as a function of ciprofloxacin concentration was found to be linear in the range of 0.5-10 µg mL-1 with r² = 0.993. Under optimal experimental conditions the method was found to be interference free. The percent relative standard deviation of the proposed method calculated against method blank was found to be 1.10%. The limit of detection (LOD) and the limit of quantitation (LOQ) for Cf (signal to noise ratio 3:1 for LOD and 10:1 for LOQ) were calculated to be 0.15 and 0.50 μg mL-1 respectively. Average percent recoveries (±SD) obtained for spiked commercial formulations; ciprol and ciproquine, and serum and urine samples were found to be in the range of 92.2±1.8% to 99.5±1.5%, 90.5±1.2% to 96.7±1.4% and 94.0±1.2% to 98.5±1.4% respectively. The data evidently prove the potential of the proposed sensor QDs in biological analysis.